A review of Dinetus Panzer, 1806 with descriptions of five new species and keys to world species (Hymenoptera, Crabronidae) - Jacobs, Hans-Joachim (Zootaxa, 2021)
A review of all known species of Dinetus Panzer, 1806 is given. Five species are described for the first time: D. arabicus sp. nov., D. deserticus sp. nov., D. jordanicus sp. nov., D. schmideggeri sp. nov. and D. vanharteni sp. nov. Separate keys for males and females of all known species are provided. The females of D. arabicus sp. nov. and D. schmideggeri sp. nov. and the males of D. cereolus Morice, 1897, D. deserticus sp. nov., D. hameri Notton, 2020, D. rakhimovi Mokrousov & Khedher, 2020, D. politus Turner, 1917 and D. vanharteni sp. nov. are unknown. With this, the total number of species increases to 21. Detailed distribution data of all examined species are presented, except the widely distributed D. pictus.